Uma abordagem SDN para virtualização de redes - PINHEIRO, Billy Anderson (Universidade Federal do Pará, 2017)
The virtual SDN networks (vSDNs) have emerged from the association of virtualization and Software-Dened Networking (SDN), providing greater control and better use of network resources. Several studies have already shown the feasibility and benets of this approach. However, the issue still lacks solutions that can virtualize a network in a scalable, intuitive and simplied manner. Thus, this thesis proposes an SDN approach to network virtualization with the aim of reducing the limitations on vSDNs. Therefore, it is suggested to adopt in network virtualization the separation between data plans (distributed) and control (centralized), the global network view and use of ow abstraction to manage the communication between the dierent points. To support our proposition, three solutions were developed: the CIM-SDN (Common Information Model for Software-Dened Networking), to enable the use of formal representation of the new elements of vSDNs; The NVP (Network Virtualization Proxy), to provide greater scalability by separating the control plane into centralized and decentralized parts; And Graph Virtualization Layer (GVL), to provide greater use of abstractions between the hypervisor and controllers, thereby simplifying the understanding and use of the network. Proof of concept tests was carried out for the three proposed solutions, demonstrating the feasibility of the approach.